Benign neural lesions of the oral and maxillofacial complex: a 48-year-retrospective study - Liliane Cristina N. Marinho; Hellen B. P. Santos; Everton F. Morais; Roseana A. Freitas (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Peripheral nerve sheath lesions are among the various diseases that can affect the nervous tissue. These neural origin lesions may occur in the maxillofacial region, although they are rare. Objective: The aim of this study was to retrospectively evaluate patient's profiles presenting benign neural tumors of the oral and maxillofacial complex and carry out comparisons with previous studies. Methods: A descriptive and retrospective study of the clinical records of patients diagnosed with benign oral and maxillofacial neural lesions at the Department of Dentistry of the Universidade Federal do Rio Grande do Norte (UFRN) was carried out, from 1970 to December 2017. Results: From a total of 15,527 histopathological records analyzed over 48 years, 57 (0.37%) corresponded to benign neural lesions, of which 24 (42.11%) were neurofibroma, 15 (26.32%) were traumatic neuroma, nine (15.79%) were neurilemoma, three (5.26%) were granular cell tumor, three (5.26%) were congenital epulis, and three (5.26%) were solitary circumscribed neuroma. Three patients (12.5%) with neurofibroma also presented type I neurofibromatosis. Most patients were female (56.66%), ranging in age from three days to 79 years old. Conclusion: The data obtained confirmed that lesions of neural origin are uncommon in the oral cavity and that neurofibroma is the most frequent, female are the most affected, and the tongue is the most prevalent affected area.